Remote training for strengthening capacity in sexual and reproductive health and rights research: a systematic review - Carla Perrotta; Vicky Downey; Darin Elabbasy; Carolyn Ingram; Chungwan Lo; Amara Naseer; Anna Thorson; Vanessa Brizuela (BMC, 2023)
Abstract Background Training has been used to develop research skills among sexual and reproductive health and rights (SRHR) researchers. Remote education may accelerate transfer of skills and reduce barriers to strengthening research capacity. This systematic review aimed to assess the effectiveness of remote training on SRHR research and describe enablers and barriers of effective remote training. Methods PubMed, Embase, and Scielo were searched up to December 2022 for studies that evaluated in any language online research training programmes either on a SRHR topic or tailored for professionals working in SRHR published since 1990. Characteristics of included studies, the programmes they evaluated, the programme's effectiveness, and reported barriers and enablers to remote learning were extracted. Three researchers synthesized and described findings on effectiveness, impact and outcomes mapping them against the Kirkpatrick model. Additionally, thematic analysis from qualitative data was conducted to identify themes relating to the barriers and enablers of remote learning. Results Of 1,510 articles retrieved, six studies that included 2,058 remote learners met the inclusion criteria. Five out of six studies described empirical improvements in participant research knowledge/skills and three studies reported improvements in attitudes/self-efficacy towards research. Follow-up surveys from four studies revealed frequent application of new research skills and improved opportunities for career advancement and publication following online trainings. Cited barriers to effective online SRHR research training included time management challenges and participants' competing professional obligations; limited opportunities for interaction; and lack of support from home institutions. Cited enablers included well-structured and clear courses, learning objectives and expectations with participants; ensuring a manageable workload; facilitating interactions with mentors and hands-on experience; and selecting programme topics relevant to participants' jobs. Conclusion Remote SRHR training can lead to improvements in research knowledge, skills, and attitudes, particularly when course learning objectives, structure, and expectations are outlined clearly, and ongoing mentorship is provided.